PERBANDINGAN PENGATURAN BEBAN PEMBUKTIAN ASAL-USUL KEKAYAAN DALAM TINDAK PIDANA KORUPSI ANTARA NEGARA INDONESIA DAN NEGARA CHINA - Chintya Bella; Susi Ramadhani; Asep Suherman (Maleo Law Journal, 2026)
The fight against corruption faces challenges in proving guilt, especially when there is a discrepancy between the wealth of public officials and their legitimate income. Shifting the burden of proof of the origin of wealth to the defendant raises legal debates regarding the principles of the presumption of innocence and due process of law. Indonesia and China both apply the reverse burden of proof mechanism in corruption cases, but with different normative constructions and legal implications. This research aims to analyze and compare the regulations on proving the origin of wealth in Indonesia and China, and to formulate the ideal direction for criminal law policy in Indonesia. This research uses a normative legal method with a statutory, comparative legal, and conceptual approach. The research results show that Indonesia adopts a limited and balanced form of reverse burden of proof, so the defendant’s obligation is limited to providing an explanation and cannot be used as a basis for punishment, which limits its effectiveness. Conversely, China applies pure reverse proof supported by an integrated surveillance system. Therefore, Indonesian criminal law policy needs to be directed toward strengthening effective and constitutional reverse burden of proof without disregarding human rights protection.